Pencabutan Status Pandemi COVID-19 oleh Presiden Jokowi Terhadap Saham-Saham JII di Bursa EfekIndonesia - Erna Listyaningsih (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2023)
Previous research discovered that the stock exchange responded to the announcement of a government policy related to the COVID-19 pandemic. The purpose of this research is to determine the impact of President Jokowi's announcement of the revocation of the COVID-19 pandemic status on stocks that are members of the Jakarta Islamic Index (JII). The event study methodology was applied to 30 JII stocks that adhere to Islamic Sharia, have high liquidity, and a large market capitalization. This study discovered that there were abnormal returns before and after President Jokowi announced the revocation of the COVID-19 pandemic status. Furthermore, a difference in stock trading volume with the average before and after the announcement was discovered. This indicates that this event contains information content, implying that investors should pay close attention to government policy announcements regarding the pandemic, which can be used as a factor in making investment decisions.